PENGARUH PERSEPSI DIRI TENTANG KOMPENSASI TERHADAP KINERJA PERAWAT DIMEDIASI OLEH MOTIVASI KERJA (Studi pada Perawat Tenaga Kontrak (non PNS) Ruang IRNA 1 Pada Rumah Sakit Umum (RSU) Dr. Saiful Anwar Kota Malang) - Sulianti, Wulan Murni; Suharto, Suharto; Yandono, Prayudo Eri (Arthavidya Jurnal Ilmiah Ekonomi, 2015)
The development of industry sectors including health services can not be separated from the demands to keep attention to the quality of its services. RSU Dr. Saiful Anwar Malang as a government-owned hospitals to always provide excellent service. Excellent service will be achieved if the employee has a good performance in providing services. Nurse's performance will be good, if the role of compensation and motivation to get attention. The purpose of this study was to analyze the effect of compensation on work motivation and performance of the Contract Workers Nurses (non-civil). The sample in this study is as much as 96 nurses. The analytical tool used is the path analysis. Based on the analysis found evidence that the compensation effect on the motivation and performance of the Contract Workers Nurses (non-civil). Work motivation is able to mediate the effect of compensation on the performance of nurses. To improve the performance of nurses Power Contract (non-civil), should the hospital need to make a policy relating to the provision of compensation both financial and non financial compensation, so as to provide motivation, which in turn can improve the performance of the Contract Workers Nurses (non-civil).Keywords: compensation, work motivation, and performance of nurses